2012
DOI: 10.1158/1078-0432.ccr-12-1202
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Prognosis in Advanced Non–Small Cell Lung Cancer Patients Receiving Platinum-Based Chemotherapy

Abstract: Purpose Genetic variation may influence chemotherapy response and overall survival in cancer patients. Experimental design We conducted a genome-wide scan in 535 advanced-stage non–small cell lung cancer (NSCLC) patients from two independent cohorts (307 from Nanjing and 228 from Beijing). A replication was carried out on an independent cohort of 340 patients from Southeastern China followed by a second validation on 409 patients from the Massachusetts General Hospital (Boston, MA). Results Consistent asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…Thus, the most advanced high throughput technologies have enabled the exploration of the cellular traits associated with increased resistance to CDDP at multiple levels. For instance, the genomic and epigenetic features associated with the loss of CDDP sensitivity have been thoroughly examined trough the search for Small Nucleotide Polymorphism (SNP) associated with CDDP resistance [1][2][3][4] or by exome sequencing. 5 Gene expression programs associated with CDDP resistance have also been intensively scrutinized by cDNA microarrays analysis or exploring alternative levels of gene expression regulation such as those mediated by microRNAs or long non-coding RNAs.…”
Section: Reportmentioning
confidence: 99%
“…Thus, the most advanced high throughput technologies have enabled the exploration of the cellular traits associated with increased resistance to CDDP at multiple levels. For instance, the genomic and epigenetic features associated with the loss of CDDP sensitivity have been thoroughly examined trough the search for Small Nucleotide Polymorphism (SNP) associated with CDDP resistance [1][2][3][4] or by exome sequencing. 5 Gene expression programs associated with CDDP resistance have also been intensively scrutinized by cDNA microarrays analysis or exploring alternative levels of gene expression regulation such as those mediated by microRNAs or long non-coding RNAs.…”
Section: Reportmentioning
confidence: 99%
“…Among these five SNPs, two SNPs, rs7629386 in CTNNB1 and rs3850370 in SNW1-ALKBH1-NRXN3, were further replicated in a Caucasian population (32). One of the strengths of this study is that the suggestive associated SNPs were not only validated in an independent sample from the Chinese population but also in another sample set from the Caucasian population.…”
Section: Lung Cancermentioning
confidence: 87%
“…Evidences revealed that patients with lung cancer with similar stages or histologic classifications have dramatically different responses to anticancer therapies and distinct survival outcomes, likely due to heterogeneity of gene/protein expression profiles (3). Established methods for predicting prognosis include the tumor, node, and metastasis (TNM) staging system; however, accumulating studies indicated that genetic biomarkers might play a vital role in cancer prognosis, according to their influences on cancer progression and treatment efficiency (4,5). Therefore, seeking distinctive molecular biomarkers and genetic variants of the key genes involved tumor initiation and progression may promote improving survival outcomes for human cancers.…”
Section: Introductionmentioning
confidence: 99%